2018
DOI: 10.1016/j.bbamem.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure and localization of a large fragment of the SARS-CoV fusion protein: Implications in viral cell fusion

Abstract: The lethal Coronaviruses (CoVs), Severe Acute Respiratory Syndrome-associated Coronavirus (SARS-CoV) and most recently Middle East Respiratory Syndrome Coronavirus, (MERS-CoV) are serious human health hazard. A successful viral infection requires fusion between virus and host cells carried out by the surface spike glycoprotein or S protein of CoV. Current models propose that the S2 subunit of S protein assembled into a hexameric helical bundle exposing hydrophobic fusogenic peptides or fusion peptides (FPs) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 77 publications
(143 reference statements)
1
23
0
Order By: Relevance
“…Clarification of the virus-host interactions will provide significant opportunities not only for the elucidation of the pathogenesis of the disease but also for the development of antiviral drugs (Mahajan et al 2018).…”
Section: E Akbulutmentioning
confidence: 99%
“…Clarification of the virus-host interactions will provide significant opportunities not only for the elucidation of the pathogenesis of the disease but also for the development of antiviral drugs (Mahajan et al 2018).…”
Section: E Akbulutmentioning
confidence: 99%
“…The functional aspects of the S protein have been known to mediate receptor binding and virus-cell fusion that occur at either the interface of the plasma membrane or within the endosomal vesicles [ 30 ]. The mechanism of membrane fusion of SARS-CoV-1 mostly belongs to the type I fusion system, where S protein of SARS-CoV-1 comprises of a number of membrane binding regions in the S2 domain identified as fusogenic peptide or FPs by several researchers [ [31] , [32] , [33] ]. Recently Bhattacharjya et al have shown that one of these fusion peptides adopts β-sheet conformation either in the presence of phosphatidylcholine or phosphatidylcholine/cholesterol comprising membrane models with the help of circular dichroism spectroscopy [ 34 ].…”
Section: The Role Of Lipids In Cov Infectionmentioning
confidence: 99%
“…We have determined 3-D structures of FPs and PTM of SARS-CoV-1 in solution of DPC detergent micelle by NMR methods [ 96 , 97 ]. The atomic resolution structure of the FP ( 770 MYKTPTLKYFGGFNFSQIL 788 ) revealed a bend helical structure presumably resulting from two Gly residues G780 and G781 at the center of the sequence ( Fig.…”
Section: Atomic-resolution Structure Of Fps Of Sars-cov-1 In Membranementioning
confidence: 99%
“…Observations of multiple adjacent fusogenic peptides in the S2 domain prompted us to examine structure and membrane localization of a 64-residue long, residues R758-E821, or LFP (long fusion peptide) in detergent micelle solution [ 97 ]. The primary structure of LFP contains FP (residues 770–788) and IFP1 (residues 798–815) with additional residues at the N and C-termini.…”
Section: Atomic-resolution Structure Of Fps Of Sars-cov-1 In Membranementioning
confidence: 99%